Profitability of small- and medium-sized enterprises in high-tech industries: the case of the biotechnology industry - Qian, Gongming; Li, Lee (Strategic management journal, 2003)
This paper investigates the profitability determinants of small- and medium-sized enterprises in high-tech industries. Literature review suggests that innovator position, market awareness, niche operation, and internationalization should have positive impacts on SMTEs' profitability. However, the empirical results partially agree with, and partially dissent from, the propositions.